(untitled) (Journal of Organizational Psychology, 2022)
While there has been some work in the past on toxic leadership in the context of corporate management, it has rarely focused on the use of this type of leadership in the implementation of a deviant system, in other words, an organization that systematically breaks the rules. The research note wishes to address the theme of toxic leadership by taking the famous case of the doping system implemented by Lance Armstrong for a decade, which allowed him to win seven successive Tours de France. The deviant system is based on a very efficient logistical bricolage thought and implemented by the toxic leader, and silently accepted by his victims.